(untitled) (Fiep Bulletin - online, 2011)
Physical education in high school, most of the time, has become for many teachers their weakness, teachers dealing with classes discouraged the practice of physical activity, largely because of work done improperly in previous years this stage of education, competition with the clubs that have attractive programs, and especially for not being one of the recommended curriculum components in vestibular and / or ENEM. One way to change this situation is the usage of different activities that help the adolescents to experience and understand the importance of physical activity for their bodies. Thus, this text aims to present the results in a survey of final year undergraduate in physical education, which used a program of recreational games in the classroom and school as a research methodology qualitative descriptive type. During the two month periods was a plan for the class containing the game as the main content. At the end of that period was applied a questionnaire, 52 students enrolled in 1st year of teaching in a state school in the city of Rio Claro, SP. The data were analyzed descriptively. Our results say that teenagers like physical education fitting for the teacher to show them the importance of using different classes that do not fall into sameness. Games can be one of the ways to accomplish this.